Hacking and Rehearsing: Experiments in Creative Tinkering. - Varela, Miguel Escobar (New Theatre Quarterly, 2016)
Hacking – improving software through a process of trial and error – is a mode of rehearsal. Such is the claim made by Miguel Escobar Varela in this article, which he furthers by exploring the similarities between the ways theatre makers and software programmers speak about their crafts. Understanding software programming as an essentially creative process should be of interest for theatre scholars, who are constantly searching for modes of academic discourse that are sensitive to the specificity of theatre. By offering examples from interface design for the study of Javanese theatre, Escobar argues that creating software, through an iterative process of trial and error, can become part of the methodological palette of theatre scholars. Miguel Escobar Varela is Assistant Professor of Theatre Studies at the National University of Singapore, and has worked as a theatre researcher, computer programmer and translator in Mexico, the Netherlands, Indonesia, and Singapore. His articles on the intersection of digital technology and theatre studies have been published in Digital Scholarship in the Humanities, Asian Theatre Journal, Performance Research, Contemporary Theatre Review and are forthcoming in TDR and Theatre Research International.